Case report: Metastatic endocrine mucin-producing sweat gland carcinoma with features of mucinous carcinoma - Sun, Yuehua; Liu, Yingchun; Li, Chuntao; Zhang, Xiaodong; Yin, Lu (Frontiers in Oncology, 2024)
Endocrine mucin-producing sweat gland carcinoma is a rare neoplasm of the skin appendages. The tumor typically exhibits slow growth and rarely metastasizes to distant sites. Herein, we report a case of a 77-year-old male who presented with a skin lesion on the right anterior chest wall 23 years ago. Fifteen years later, surgical excision was performed, and the pathological diagnosis was endocrine mucin-producing sweat gland carcinomas. However, the histopathological examination revealed a coexistence of endocrine mucin-producing sweat gland carcinomas and mucinous carcinoma components. Over the past 2 years, the patient developed lymph node metastasis in the right axilla, local recurrence on the right chest wall, and distant skin metastasis. The histopathological type of the lymph node metastasis was consistent with the primary tumor, while the recurrent and skin metastatic lesions exhibited mucinous carcinoma. To our knowledge, this is the first reported case of endocrine mucin-producing sweat gland carcinoma with distant skin metastasis, characterized by two distinct carcinoma components in the histopathological morphology.